Kemampuan Bernalar Ilmiah Mahasiswa Pada Mata Kuliah Kimia Teknik - Maya Erliza Anggraeni (FKIP Universitas Palangka Raya, 2018)
The ability to reason scientifically (scientific reasoning) is needed in understanding science, including chemistry. The patterns of scientific reasoning enable students to analyze facts or information logically and systematically. Students with good scientific reasoning skills are expected to be able to construct concepts better. This study aims to describe the scientific reasoning ability of Mechanical Engineering Education students in Engineering Chemistry courses. Research subjects numbered 65 people. Students' scientific reasoning abilities are measured by the Classroom Test of Scientific Reasoning (CTSR). Based on this CTSR test score, the level of student development can be categorized into four levels of development, namely the level of concrete, low formal, upper formal and post formal. The results showed that as many as 89% of students were still at the level of concrete reasoning and only 11% had reached the level of reasoning low formal. This shows the level of scientific reasoning ability of students is still low and there is a delay in the development of reasoning ability. The lowest type of reasoning is the probability reasoning pattern and the conservation reasoning pattern is the reasoning most mastered by students.